Pengaruh Kepemimpinan Motivasi Kerja dan Kompetensi Terhadap KinerjaPegawai Pada Dinas Perhubungan Kabupaten Ogan Ilir - Kartika, Ida; Idris, Muhammad; Moelyati, Trisniarty Adjeng (Jurnal Nasional Manajemen Pemasaran dan SDM, 2024)
This study aims to determine leadership, work motivation, and Competency in employee performance at the Ogan Ilir Regency Transportation Office. The object of this study is an employee of the Ogan Ilir Regency Transportation Office. The research method used is associative research using primary and secondary data. The population in this study was 179 employees at the Ogan Ilir Regency Transportation Office; the sample was taken using the Slovin formula, so the number of samples used was 128 employees. The analysis technique used is multiple linear regression. The results of this study showed that 1) simultaneously, Leadership, Work Motivation, and Competency have a significant effect on the performance of employees of the Ogan Ilir District Transportation Office. 2) Leadership has a significant effect on the performance of employees of the Ogan Ilir District Transportation Office.  3) Work Motivation does not have a significant effect on the performance of employees of the Ogan Ilir Regency Transportation Office. 4) Competency has a significant effect on the performance of employees of the Ogan Ilir Regency Transportation Office.